Ion-doped liquid-crystal cell with low opaque-state specular transmittance based on electro-hydrodynamic effect. (March 2018) - Huh, Jae-Won; Kim, Jin-Hun; Oh, Seung-Won; Ji, Seong-Min; Yoon, Tae-Hoon
Abstract: We demonstrate an ion-doped liquid-crystal (LC) cell that can provide a very low specular transmittance in the opaque state using the electro-hydrodynamic effect. In the opaque state, the LC and dye molecules are oriented randomly in planes parallel to the substrates because of the electrohydrodynamic effect. We found that the total transmittance of an ion-doped LC cell is almost the same as that of a light shutter based on light absorption and its haze value is the same as that of a light shutter based on light scattering. Moreover, an ion-doped LC cell can be fabricated without an ultraviolet curable process. Owing to its excellent opaque state properties, an ion-doped LC cell can be used in see-through display and smart-window applications. Graphical abstract: Highlights: We demonstrate an LC cell that can provide a very low total transmittance. For opaque state, we use negative LC with dye and electro-hydrodynamic effect. Most of the dye molecules are oriented parallel to the substrates. Randomly distributed negative LCs with small domains scatter the incident light. It can be fabricated without an ultra-violet curing process.